Investigation of some factors influencing the formation of monocalcium phosphate in aqueous medium - Duc , Ta Hong; Bac, Nguyen Quang (Vietnam Journal of Science and Technology, 2019)
Some factors that influence to the formation of monocalcium phosphate in aqueous solution have been investigated in detail. The results show that reaction temperature, and initial concentration of phosphoric acid, as well as reaction duration determine the content of monocalcium phosphate in the processing mixture. The information in this report will be useful, and the basis for the design of the synthesis reactor in the monocalcium phosphate production